Test Design and Sample Preparation Procedure for Experimental Investigation of Hydraulic Fracturing Interaction Modes - Sarmadivaleh, Mohammad; Rasouli, V. (Springer-Verlag Wien, 2014)
Hydraulic fracturing is a complex operation which is influenced by several factors including the formation properties, state of stresses in the field, injecting fluid and pumping rate. Before carrying out the expensive fracturing operation in the field, it would be useful to understand the effect of various parameters by conducting physical experiments in the laboratory. Also, laboratory experiments are valuable for validating numerical simulations. For this purpose, laboratory experiments may be conducted on synthetically made samples to study the effect of various parameters before using real rock samples, which may not be readily available. To simulate the real stress conditions in the field, experiments need to be conducted on cube-shaped samples on which three independent stresses can be applied. The hydro-mechanical properties of a sample required for modelling purposes and the design of a scaled hydraulic fracturing test in the laboratory can be estimated by performing various laboratory experiments on cylindrical plugs. The results of laboratory experiments are scaled to field operation by applying scaling laws. In this paper, the steps to prepare a cube-shaped mortar sample are explained. This follows a review of the sample set-up procedure in a true tri-axial stress cell for hydraulic fracturing experiments. Also, the minimum tests on cylindrical plugs required to estimate the hydro-mechanical properties of the rock sample are explained. To simulate the interaction mode when a hydraulic fracture approaches an interface in the laboratory, the procedure for producing samples with parallel artificial fracture planes is explained in this paper. The in-fill material and the angle of fracture planes were changed in different samples to investigate the effect of interface cohesion and the angle of approach on the interaction mechanism.